PENERAPAN PENDEKATAN KETERAMPILAN PROSES SAINTIFIK MELALUI MEDIA VIDEO TERHADAP HASIL BELAJAR MENULIS RINGKASAN TEKS EKSPLANASI DI SDN TAENG KABUAPTEN GOWA - Ulviani, Maria; Rosmalina Kemala; Hilda Hafid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe: (1) the level of learning outcomes in writing explanatory text summaries with a scientific process skills approach through video media, (2) the level of learning outcomes in writing explanatory text summaries with conventional methods, and (3) the effectiveness of the scientific process skills approach through video media in improving students' learning outcomes in writing explanatory text summaries. This study used a quasi-experimental method with a non-equivalent control group design. The study population was all fifth grade students of SDN Taeng, Gowa Regency in the 2020/2021 academic year, totaling 56 students. The study sample consisted of an experimental class and a control class that were randomly selected after going through a homogeneity test of initial ability to write explanatory text summaries. The results of the study showed that: (1) the level of learning outcomes in writing summaries of explanatory texts of students with the scientific process skills approach through video media was in the medium category with an average value of 66.96, (2) the level of learning outcomes in writing summaries of explanatory texts of students with the conventional method was in the low category with an average value of 59.68, and (3) the scientific process skills approach through video media was effective in improving learning outcomes in writing summaries of explanatory texts of students, with the results of statistical tests showing that the t-count value (13.336) was greater than the t-table value (2.048) at a significance level of 0.05.